2005
DOI: 10.1016/j.jeurceramsoc.2005.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the yttria powder morphology on its densification ability

Abstract: :The present paper shows that we can predict the densification capacity of an yttria powder in relation with its grain shape by using a simple thermodynamic model. All other parameters, such as temperature, time, sintering atmosphere and nature of the powder are fixed. The values of the relative density and grain size of the final ceramic strongly depend on the shape of the grain of the initial powder. A simple model is proposed to understand these differences and to give tools to predict, step by step the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…These collapsed powders are then sintered without significant grain growth. Dupont et al 58 proposed a similar mechanism for yttria powders, in which the first step during sintering corresponded to the rearrangement of individual particles into a full packing of spheres to eliminate porosity, followed by full densification and grain growth.…”
Section: Resultsmentioning
confidence: 99%
“…These collapsed powders are then sintered without significant grain growth. Dupont et al 58 proposed a similar mechanism for yttria powders, in which the first step during sintering corresponded to the rearrangement of individual particles into a full packing of spheres to eliminate porosity, followed by full densification and grain growth.…”
Section: Resultsmentioning
confidence: 99%
“…After calcination, it was observed that the individual particles which occurred at the stage of crystal growth during heat treatment. At high temperature, the flaky and platelets structure broke into nanometric spherical particles (Dupont et al, 2005). It was also observed that the agglomerates of thin flakes with a smooth surface, perforated by many large pores.…”
Section: Sem and Tem Studiesmentioning
confidence: 96%
“…The rare‐earth oxide powders can be prepared in many ways, for example, precipitation, hydrothermal synthesis, solgel, and combustion method …”
Section: Introductionmentioning
confidence: 99%